2017
DOI: 10.14569/ijacsa.2017.081042
|View full text |Cite
|
Sign up to set email alerts
|

Modeling House Price Prediction using Regression Analysis and Particle Swarm Optimization Case Study : Malang, East Java, Indonesia

Abstract: Abstract-House prices increase every year, so there is a need for a system to predict house prices in the future. House price prediction can help the developer determine the selling price of a house and can help the customer to arrange the right time to purchase a house. There are three factors that influence the price of a house which include physical conditions, concept and location. This research aims to predict house prices based on NJOP houses in Malang city with regression analysis and particle swarm opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…In addition, the impact of various attributes on specific model have also been evaluated and debated. [38] Locational and structural attributes - [3] Locational and structural attributes 0.267 [39] Locational attributes - [40] Locational attributes - [10] Economic attributes - [41] Locational, structural and neighborhood attribute - [11] Locational and structural attributes 0.3079 [7] Copyright Based on reviewing numerous papers, there are several attributes used by researchers in their work to forecast house prices. All of these attributes can be divided into 4 main categories which are locational, structural, neighborhood and economic attributes.…”
Section: Finding and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the impact of various attributes on specific model have also been evaluated and debated. [38] Locational and structural attributes - [3] Locational and structural attributes 0.267 [39] Locational attributes - [40] Locational attributes - [10] Economic attributes - [41] Locational, structural and neighborhood attribute - [11] Locational and structural attributes 0.3079 [7] Copyright Based on reviewing numerous papers, there are several attributes used by researchers in their work to forecast house prices. All of these attributes can be divided into 4 main categories which are locational, structural, neighborhood and economic attributes.…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Location is considered to be the most significant feature of house price determination [6,[9][10][11]. [12] in his study also observed the significant of location attributes in deciding house price.…”
Section: A Locationalmentioning
confidence: 93%
See 3 more Smart Citations